Sensitivity of Nursing Home Cost Comparisons to Method of Dementia Diagnosis Ascertainment. (2009) - Gruber-Baldini, Ann L.; Stuart, Bruce; Zuckerman, Ilene H.; Hsu, Van Doren; Boockvar, Kenneth S.; Zimmerman, Sheryl; Kittner, Steven; Quinn, Charlene C.; Hebel, J. Richard; May, Conrad; Magaziner, Jay
Abstract : This study compared the association of differing methods of dementia ascertainment, derived from multiple sources, with nursing home (NH) estimates of prevalence of dementia, length of stay, and costs an understudied issue. Subjects were 2050 new admissions to 59 Maryland NHs, from 1992 to 1995 followed longitudinally for 2 years. Dementia was ascertained at admission from charts, Medicare claims, and expert panel. Overall 59.5% of the sample had some indicator of dementia. The expert panel found a higher prevalence of dementia (48.0%) than chart review (36.9%) or Medicare claims (38.6%). Dementia cases had lower relative average per patient monthly costs, but longer NH length of stay compared to nondementia cases across all methods. The prevalence of dementia varied widely by method of ascertainment, and there was only moderate agreement across methods. However, lower costs for dementia among NH admissions are a robust finding across these methods.